Using Audio-Visual Aids to Improve the Concept of Dentition in Second Year Science Students at Mfantsipim School - Amoah, John Ekow Mbir (Advances in Social Sciences Research Journal, 2025)
This action research investigated the effects in using audio-visual materials on the academic performance of second year science students of Mfantsipim School in the concept dentition in humans. An action research design was used with a sample of 43 students. The main instruments for data gathering were tests (pre-test and post-test) The pre-test results revealed generally low performance, with a mean score of 10.77, whereas after the intervention with audio-visual aids (videos, diagrams, interactive presentations), the post-test mean rose significantly to 16.63. A paired-samples t-test showed that this improvement was statistically significant (t (42) = 15.842, p = 2.54 × 10⁻¹⁹ < 0.05), confirming that the intervention impacted positively on student achievement. The results further demonstrated that fewer students scored in the lower scores after the intervention, while more attained higher marks (including scores of 26–30, which was absent in the pre-test). The findings suggest that the use of audio-visual materials not only enhanced comprehension and retention but also fostered greater student engagement and interest in science learning. It was recommended that, biology teachers should adopt audio-visual materials in teaching complex topics. Whilst, regular workshops should be organized to train teachers in the effective use of technology in teaching.